Evolution of T. simplex, Jenkins from the Middle Miocene to the Early Pliocene and its Chances of Becoming a Distinct Subspecies - Pandita, Hita; Al Hussein Flower Risqy (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
The presence of Turritellidae fossils in rocks is very important, because they are index fossils at the levels of mollusk biostratigraphy in Indonesia. However, its use is not yet optimal, due to one of the reasons being different names for the same specimen or conversely giving the same species name to different forms. One example is Turritella simplex. This research is intended to re-identify Turritella simplex originating from two populations that have different shapes and sizes. The goal is to find out whether the two populations are the same or different species. The method used is the analysis of the similarity of the identification parameters and the similarity test of the biometric patterns. The results showed that the two populations from Cilanang and Meningten showed similar morphological identification parameters, but differen in biometric aspects. The recommendation from this research is to divide it into two different subspecies, and can be represented at different biostratigraphic levels. Both populations show an evolutionary process in terms of biometry and morphology.